Adapting to social media: the influence of online reviews on tourist behaviour at a world heritage site in China. Issue 10 (3rd October 2021) - Xu, Han; Lovett, Jon; Cheung, Lewis T. O.; Duan, Xialei; Pei, Qing; Liang, Dan
ABSTRACT : Extending narrative transportation theory, the purpose of this study is to examine the effect of online reviews on destination choice and purchasing behaviour at a destination and to clarify the role of prior destination knowledge and perceived usefulness of online reviews. Data were collected from 432 tourists in Gulangyu, a UNESCO World Heritage Site in China. The results of structural equation modelling analysis validate the positive effect of online reviews on tourists' destination choice and purchasing behaviour. This study offers both theoretical and policy implications to understand how tourists reference online reviews to make travel-related decisions.